Melatonin as an Antitumor Agent against Liver Cancer: An Updated Systematic Review - Paula Fernández-Palanca; Carolina Méndez-Blanco; Flavia Fondevila; María J. Tuñón; Russel J. Reiter; José L. Mauriz; Javier González-Gallego (MDPI AG, 2021)
Melatonin (N-acetyl-5-methoxytryptamine) is an indoleamine with antioxidant, chronobiotic and anti-inflammatory properties; reduced levels of this hormone are associated with higher risk of cancer. Several beneficial effects of melatonin have been described in a broad number of tumors, including liver cancers. In this work we systematically reviewed the publications of the last 15 years that assessed the underlying mechanisms of melatonin activities against liver cancers, and its role as coadjuvant in the treatment of these tumors. Literature research was performed employing PubMed, Scopus and Web of Science (WOS) databases and, after screening, 51 articles were included. Results from the selected studies denoted the useful actions of melatonin in preventing carcinogenesis and as a promising treatment option for the primary liver tumors hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA), either alone or in combination with other compounds. Different processes were modulated by the indole, such as inhibition of oxidative stress, proliferation, angiogenesis and invasion, promotion of immune system response, cell cycle arrest and apoptosis, as well as recovery of circadian rhythms and autophagy modulation. Taken together, the present systematic review highlights the evidence that document the potential role of melatonin in improving the landscape of liver tumor treatment.